Warmer incubation temperatures and later lay‐orders lead to shorter telomere lengths in wood duck (Aix sponsa) ducklings. Issue 1 (10th October 2022) - Hope, Sydney F.; Angelier, Frédéric; Ribout, Cécile; Groffen, Jordy; Kennamer, Robert A.; Hopkins, William A.
Abstract: The environment that animals experience during development shapes phenotypic expression. In birds, two important aspects of the early‐developmental environment are lay‐order sequence and incubation. Later‐laid eggs tend to produce weaker offspring, sometimes with compensatory mechanisms to accelerate their growth rate to catch‐up to their siblings. Further, small decreases in incubation temperature slow down embryonic growth rates and lead to wide‐ranging negative effects on many posthatch traits. Recently, telomeres, noncoding DNA sequences at the end of chromosomes, have been recognized as a potential proxy for fitness because longer telomeres are positively related to lifespan and individual quality in many animals, including birds. Although telomeres appear to be mechanistically linked to growth rate, little is known about how incubation temperature and lay‐order may influence telomere length. We incubated wood duck ( Aix sponsa ) eggs at two ecologically‐relevant temperatures (34.9°C and 36.2°C) and measured telomere length at hatch and 1 week after. We found that ducklings incubated at the lower temperature had longer telomeres than those incubated at the higher temperature both at hatch and 1 week later. Further, we found that later‐laid eggs produced ducklings with shorter telomeres than those laid early in the lay‐sequence, although lay‐order was not related to embryonic developmental rate. This study contributes to our broader understanding of how parental effects can affect telomere length early in life. More work is needed to determine if these effects on telomere length persist until adulthood, and if they are associated with effects on fitness in this precocial species. Abstract : Wood duck eggs incubated at a slightly warmer temperature and laid later in the lay‐sequence produced ducklings with shorter telomeres at hatch and 1 week later, compared to those incubated at a colder temperature or laid earlier in the sequence. Research highlights: Wood duck eggs incubated at a slightly warmer temperature and laid later in the lay‐sequence produced ducklings with shorter telomeres at hatch and 1 week later, compared to those incubated at a colder temperature or laid earlier in the sequence.